Tracing the new economic geography of borders in Europe - George Petrakos; Lefteris Topaloglou (European Regional Science Association (ERSA), 2005)
Borders and border regions receive a special attention in the new post-1989 European architecture characterized by the processes of integration, transition and enlargement. What is actually happening to borders and border regions within this new environment? Are borders being abolished, weakened or are they being reproduced under a different pattern? What are the determinant factors which define the level and type of cross border interaction? This paper attempts to shed some light into the dynamics, perceptions and the new challenges concerning the "border phenomenon”. An empirical evidence is based on a survey at the Greek-Albanian-FYROM-Bulgarian border zone by analysing survey data. The survey, aims to evaluate a) the level and the type of cross-border interaction b) the obstacles and the limit of greater cross border interaction c) the existing perceptions and images of the other side of the borders d) the effectiveness of policies to stimulate interaction, e) the effects (positive and negative) of greater interaction on the border regions, f) the effects of EU enlargement on the c-b regions.
Keywords: 330